A polysaccharide from dried aerial parts of Agrimonia pilosa: Structural characterization and its potential therapeutic activity for steroid‑induced necrosis of the femoral head (SANFH) - Huang, Wei; Wang, Haili (Carbohydrate polymers, 2019)
In this study, one homogeneous polysaccharide (APP-AW), with an average molecular weight of 9550 Da, was purified from Agrimonia pilosa. Analysis by gas chromatography (GC), methylation, UV, Infrared spectra (IR), 1D and 2D nuclear magnetic resonance (NMR) spectroscopy indicated that APP-AW was a β-(1 → 3)-d-glucan. The effect of APP-AW on dexamethasone (Dex)-induced apoptosis in osteoblasts was also examined. Pretreatment of APP-AW (100 μg/ml) significantly attenuated cell loss and apoptosis induced by Dex (1 μM) in osteoblasts as determined by MTT, Annexin V-FITC/ propidium iodide (PI) and Transferase (TdT)-mediated dUTP nick end labeling (TUNEL) staining assay. Collectively, the present study demonstrated that APP-AW might be an alternative therapeutics for the treatment of SANFH via reducing Dex‑induced bone cellular apoptosis.
Available online: 04 March 2019
Gesehen am 16.04.2019